VectorNet: Putting Vectors on the Map - Braks, Marieta; Schaffner, Francis; Medlock, Jolyon M.; Berriatua, Eduardo; Balenghien, Thomas; Mihalca, Andrei Daniel; Hendrickx, Guy; Marsboom, Cedric; Van Bortel, Wim; Smallegange, Renate C.; Sprong, Hein; Gossner, Céline M.; et al. (Frontiers in Public Health, 2022)
Abstract Public and animal health authorities face many challenges in surveillance and control of vector-borne diseases. Those challenges are principally due to the multitude of interactions between vertebrate hosts, pathogens and vectors in continuously changing environments. VectorNet, a joint project of the European Food Safety Authority (EFSA) and the European Centre for Disease Prevention and Control (ECDC) facilitates risk assessments of VBD threats through the collection, mapping and sharing of distribution data for ticks, mosquitoes, sand flies and biting midges that are vectors of pathogens of importance to animal and/or human health in Europe. We describe the development and maintenance of this One Health network that celebrated its 10th anniversary in 2020 and the value of its most tangible outputs, the vector distribution maps, that are freely available online and its raw data on request. VectorNet encourages usage of these maps by health professionals and participation, sharing and usage of the raw data by the network and other experts in the science community. For the latter, a more complete technical description of the mapping procedure will be submitted elsewhere.